IS STARCH ONLY A VISUAL INDICATOR FOR IODINE IN THE BRIGGS-RAUSCHER OSCILLATING REACTION? - CSEPEI, Lénárd-István; BOLLA, Carol-Csaba (Studia Universitatis Babeș-Bolyai Chemia, 2015)
In this work, we studied the effect of malonic acid concentration on the Briggs-Rauscher oscillating reaction both in absence and in presence of starch, which acts as indicator for the iodine intermediate. For the starch free mixtures, the number of oscillations and the oscillation time increased with the increase of initial malonic acid concentration, while the period time showed the opposite trend. When starch was also present in the Briggs-Rauscher mixture, the number of oscillations, the oscillation time and period length were higher in comparison with the starch free mixtures with the same initial malonic acid concentration. In presence of starch, within one oscillation period, the iodine consumption segment was also longer compared to those measured for the starch free mixtures. This suggests that the starch is not only a simple visual indicator for the iodine intermediate, but it probably acts as a reservoir for iodine due to the starch-triiodide equilibrium during each oscillation cycle. As such, the starch may influence the kinetics of the reaction steps involving the iodine intermediate. Finally, we present a simple method for the treatment of the residual Briggs-Rauscher mixture which enables the removal of the strong acid, the oxidizing agents and the quantitative recovery of the Mn2+ catalyst in form of MnO2. Thereby, this method enables the minimization of the environmental effect of the residual mixture before disposing of it.